PENGARUH KECERDASAN INTELEKTUAL (IQ) DAN KECERDASAN EMOSIONAL (EQ) TERHADAP KINERJA - Muhamad Irpan Nurhab; Lizar Alfansi; Fahrudin Js Pareke; Syaiful Anwar (Jurnal Manajemen dan Bisnis, 2022)
To improve the quality of education in SMA Muhammadiyah 4 Bengkulu City, the main focus must be on improving the performance of its human resources. Among them are terms Intellectual Intelligence (IQ) and Emotional Intelligence (EQ). The purpose of this study is to see the influence of intellectual intelligence (IQ) partially on performance, the effect of emotional intelligence (EQ) on performance, and the effect of intellectual intelligence (IQ) and emotional intelligence (EQ) simultaneously on performance. The population in this study were 43 educators (teachers) and education staff at SMA Muhammadiyah 4 Bengkulu City. This research uses multiple linear regression analysis methods. Methods of data collection using a questionnaire. The results of hypothesis testing indicate that Intellectual Intelligence (IQ) has a positive and significant effect on Performance, Emotional Intelligence (EQ) has a positive and significant effect on Performance. And Intellectual Intelligence (IQ) and Emotional Intelligence (EQ) have a positive and significant effect simultaneously on performance.